Upgraded Whale Optimization Algorithm for fuzzy logic based vibration control of nonlinear steel structure. (1st August 2019) - Azizi, Mahdi; Ejlali, Reza Goli; Mousavi Ghasemi, Seyyed Arash; Talatahari, Siamak
Highlights: Upgraded Whale Optimization Algorithm (UWOA) is proposed. Optimal design of fuzzy logic controller is obtained using the proposed method. The performance of the upgraded method is compared with various algorithms. Nonlinear behavior of the structure is considered in optimization process. Abstract: In the case of controlling the seismic vibration of a structure, reliance on human knowledge and expert in the formulation of a fuzzy logic controller leads to non-optimal solutions, which makes the use of control devices and algorithm unreasonable. In most cases, the calculated control force for high-rise buildings is very large and the controlled response of the structure is not significantly decreased. To overcome these drawbacks, the parameter tuning of fuzzy systems with optimization algorithms are necessary. This paper focuses on the optimization of a fuzzy controller applied to a seismically excited nonlinear steel building. In the majority of cases, this problem is formulated based on the structural responses in linear range, however in this paper, objective functions and the performance criteria are considered with respect to the nonlinear responses of the structure. An Upgraded Whale Optimization Algorithm is proposed and utilized as the optimization technique for parameter tuning of the fuzzy controller. The performance of the presented upgraded algorithm is compared with the standard Whale Optimization Algorithm and eight different metaheuristic algorithms. The obtained results prove that the upgraded method is capable of providing competitive results.